MASKULINISASI IKAN NILA MERAH (Oreochromis sp.) MENGGUNAKAN PROPOLIS DENGAN METODE PERENDAMAN LARVA DAN PAKAN - Witoko, Pindo; Noor, Nuning Mahmudah; Aziz, Rahmadi; Pramesthye, Errisha Ardhia; Pratama, Rizal Aditia Pratama (Jurnal Perikanan Terapan, 2024)
Red tilapia (Oreochromis sp.) is the result of a cross between tilapia O. mozambicus and fish. tilapia O. niloticus. The advantages of tilapia are its relatively fast growth and relatively easy maintenance, as well as having a significant tolerance to environmental conditions. The growth rate of male fish is higher than that of females. Hormonal stimulants for male sexual orientation can be derived from natural ingredients, namely propolis. Propolis has advantages, including being safe for consumption, relatively inexpensive, and environmentally friendly. Treatment of propolis through immersion and artificial feed on red tilapia (Oreochromis sp.) seeds at a dose of 0.1 ml/L and 2.7 ml/kg of feed resulted in a male sex percentage of 85%, SR 100%, FCR treatment A (1 .43) and treatment B (1.34).